Hubungan Faktor Usia Ibu Hamil Terhadap Jenis Persalinan Di Klinik Josef Tuda Tombatu - Abuno, Florensia Frisilia; Alfitri, Rosyidah; Wijayanti, Tut Rayani Akhsohini (Madu : Jurnal Kesehatan, 2024)
Childbirth is an important process for a mother because it is a natural process that expends a lot of energy and undergoes physiological and psychological changes. The optimal productive age for healthy reproduction is between 20 and 35 years. Childbirth can be done in two ways: vaginal delivery, or normal delivery; perabdominal delivery, or sectio caesarea delivery, is an operation that removes the baby through an incision in the abdominal wall and uterus. During labor, the uterus must remain intact and the fetus must weigh more than 500 grams. Objective: To Analyze the Effect of Age Factors of Pregnant Women on Types of Methods: This study is a quantitative study with an observational analytical design. The population in this study were mothers in labor. The sample in this study was 26 samples. Samples were taken using the Purposive sampling technique. Data collection was obtained from medical record data. Bivariate analysis using Chi Square. Results: The results of the Chi Square analysis test showed that there was an effect of the age factor of pregnant women on the type of delivery with a p value = 0.03. Thus, pregnant women in the high-risk age group (<20 and >35 years) have a 2-fold risk of abdominal delivery compared to those of reproductive age (20-35 years). Conclusion: There is an influence of the age factor of pregnant women on the type of delivery at the Josef Tuda Tombatu Clinic.